(untitled) (Comprehensive Journal of Science, 2025)
This study examines the impact of psychological awareness programs on improving the lifestyle of diabetic patients, focusing on evaluating the effectiveness of these programs in modifying health behaviors and enhancing patients’ psychological and social adaptation The research aims to identify the most influential components of such programs and to clarify the factors that facilitate or hinder patients’ benefit from them The study also investigates the role of psychological support and continuous education in promoting treatment adherence and improving patients’ health-related quality of life Furthermore, it highlights the importance of sustainably integrating psychological awareness programs into the healthcare system to ensure the continuity of their positive impact